Teaching English for Tourism in order to Cater to the Specific Requirements of English majors at Ho Chi Minh City University of Industry and Trade - Hien , Nguyen Thanh (Journal of Knowledge Learning and Science Technology ISSN: 2959-6386 (online), 2024)
This study looks at what students need in English for tourism classes at Ho Chi Minh City University of Industry and Trade (HUIT). It shows that there are three ways to do a needs analysis: target situation analysis(TSA), present situation analysis(PSA), and holistic analysis. As part of this study, the author polled 180 students online to find out what HUIT English majors need for their English for tourism learning. The results show that the students think they need to work on being able to communicate better in English and learning more about tourism. They plan to include more project work to give students more chances to use the language in real life. The results from this study can be used to modify the present ESP courses to meet the needs of students learning English for tourism at HUIT.
Keywords: Needs analysis; TSA; PSA; Holistic analyis; English for Tourism; ESP material